2016
DOI: 10.1021/acsnano.5b07533
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Assisted Assembly of Modular 3D Plasmonic Raspberry-like Core/Satellite Nanoclusters: Correlation of Structure and Optical Properties

Abstract: We present a bottom-up assembly route for a large-scale organization of plasmonic nanoparticles (NPs) into three-dimensional (3D) modular assemblies with core/satellite structure. The protein-assisted assembly of small spherical gold or silver NPs with a hydrophilic protein shell (as satellites) onto larger metal NPs (as cores) offers high modularity in sizes and composition at high satellite coverage (close to the jamming limit). The resulting dispersions of metal/metal nanoclusters exhibit high colloidal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
180
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(181 citation statements)
references
References 66 publications
0
180
0
1
Order By: Relevance
“…The path to hierarchical organization of nanoscale particles in liquid medium offers great opportunities for the development of new chemical methods of colloidal assembly . Additionally, sophisticated design provides superstructures with physicochemical properties, which are not only superior, but also do not arise in the constituent particles.…”
Section: Introductionmentioning
confidence: 99%
“…The path to hierarchical organization of nanoscale particles in liquid medium offers great opportunities for the development of new chemical methods of colloidal assembly . Additionally, sophisticated design provides superstructures with physicochemical properties, which are not only superior, but also do not arise in the constituent particles.…”
Section: Introductionmentioning
confidence: 99%
“…The term “soft photonics” refers primarily to the realization of photonic systems from various individual components such as gratings, photonic crystals, plasmonic structures, microlenses, and metamaterials, which are formed fully or partially from a broad range of soft materials. These materials include fluids, DNA assemblies, hydrogels, flexible and stretchable elastomers, photo‐reconfigurable polymers, biological components, and colloidal suspensions . They are processed using suitable soft matter processing strategies, including self‐assembly, reaction–diffusion processes, nanoimprinting/transfer printing,…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies have demonstrated various kinds of core-satellite nanostructures, some of the studies only focus on the synthesis and plasmonic properties of the nanostructures but did not use the nanostructures for SERS 24,25,32,4247 . Some other studies used core-satellite nanostructures for enhancing Raman reporter molecules that were placed at the hot spots but not for determining the concentrations of molecules 30,31,33,34,4850 .…”
Section: Introductionmentioning
confidence: 99%